The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1096-3642.2007.00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the subgeneric division of Arenopontia Kunz, 1937: resurrection of Psammoleptastacus Pennak, 1942, re-examination of Neoleptastacus spinicaudatus Nicholls, 1945, and proposal of two new genera and a new generic classification (Copepoda, Harpacticoida, Arenopontiidae)

Abstract: A new generic classification is proposed for the 32 valid species of the interstitial marine family Arenopontiidae (Copepoda, Harpacticoida), primarily based on new observations of type species and reliable descriptions from the literature. The subgeneric division of Arenopontia Kunz, 1937 is abolished, and both Arenopontia and Neoleptastacus Nicholls, 1945 are upgraded to full generic rank. Arenopontia is restricted to the subterranea group, comprising Arenopontia subterranea Kunz, 1937 (type), Arenopontia pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…List of harpacticoids and their localities determined in these study and comparison with the previous records from Turkey. A: Noodt [8], B: Karaytuğ & Huys [25], C: Huys et al [26], D: Karaytuğ & Sak [27], E: Sak et al [28], F: Pulat et al [29], G: Alper et al [22], H: Sönmez et al [30], I: Kaymak et al [31], J: Sönmez et al [32], K: Köroğlu et al [33], L: Alper et al [34], M: Sönmez et al [35], N: Karaytuğ & Koçak [11], O: Yıldız & Karaytuğ [12], P: Sönmez et al [36], Q: Alper et al [13]. ---------- ---------- ).…”
Section: Resultsmentioning
confidence: 99%
“…List of harpacticoids and their localities determined in these study and comparison with the previous records from Turkey. A: Noodt [8], B: Karaytuğ & Huys [25], C: Huys et al [26], D: Karaytuğ & Sak [27], E: Sak et al [28], F: Pulat et al [29], G: Alper et al [22], H: Sönmez et al [30], I: Kaymak et al [31], J: Sönmez et al [32], K: Köroğlu et al [33], L: Alper et al [34], M: Sönmez et al [35], N: Karaytuğ & Koçak [11], O: Yıldız & Karaytuğ [12], P: Sönmez et al [36], Q: Alper et al [13]. ---------- ---------- ).…”
Section: Resultsmentioning
confidence: 99%
“…Distribution in Turkey: Aegean Sea [37,38], Black Sea [20]. Distribution in Turkey: Aegean Sea [30,37,38], The Black Sea [18].…”
Section: St5 (6♀♀)mentioning
confidence: 99%
“…Karaytuğ and Sak [17] recorded 37 species and 1 subspecies belonging to 21 families from the Aegean and Sea of Marmara coasts of Balıkesir province. Psammoleptastcus barani was described from the Black Sea coast (Sahilköy/Istanbul) [18]. Sak et al [19] reported the first record of Pseudoleptomesochrella halophila in Turkey from the coasts of Bartın and Kastamonu and presented the redescription of the genus Pseudoleptomesochrella.…”
Section: Introductionmentioning
confidence: 99%